Mapping China Peasants, Migrant Workers and Informal Labor (Volume 1) - Wu, Chongqing (Brill, 2016)
This collection includes seven articles from the journal Open Times, a window into contemporary Chinese academic trends. All the articles deal with the topic of "peasants, migrant workers and informal labor," but each has a different emphasis. It illustrates various ways that people from a countryside make use of local social resources to seek out ways to making a living. In these models, we can still see traditional social networks, various degrees of ties based on kinship and locality, and the existence of humans as social groups. It also analyzes Dagongmei's collective actions to fight against the capital and patriarchy, workers' collective resistance at OEM factories, and the impacts of labor migration on rural poverty and inequality.